(3TQM OjhGf GeQF GdbjS Hf MLQ GdcfOis - (3CHi HcQ YGUe Hf CjhH GdHWdjhSjs; (3GeQD GdbjS , GeQD GdbjSs ((3eMeO Hf YHO GdYRjR GdeYQha HGHf GdHSGeg s)
(3ChdgG (B:s
(3HMeO Gddg fSJaJM hHGdUdg Ydi eMeO fSJfLM CYde CHbGc Gddg Cf ddTYQGA CZQGVkG JfRd YfgG GdYdeGA s
(3BNQgG (B:s
(3hbGd jgLh bjUQ edc GdQhe(B: (3Efi MdaJ jejfkG ZjQ cGPHI Cfc Cbda EdG eGLfi GdbeQ ceG jdGJ HQCS Gdadcg GdhHQ Je TYQ GeQF GdbjS Hf MLQ, hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3QhGjI GdCUeYis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs